2014
DOI: 10.1007/s00247-014-3246-z
|View full text |Cite
|
Sign up to set email alerts
|

4-D flow magnetic resonance imaging: blood flow quantification compared to 2-D phase-contrast magnetic resonance imaging and Doppler echocardiography

Abstract: Background Doppler echocardiography (echo) is the reference standard for blood flow velocity analysis, and two-dimensional (2-D) phase-contrast magnetic resonance imaging (MRI) is considered the reference standard for quantitative blood flow assessment. However, both clinical standard-of-care techniques are limited by 2-D acquisitions and single-direction velocity encoding and may make them inadequate to assess the complex three-dimensional hemodynamics seen in congenital heart disease. Four-dimensional flow M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
55
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 35 publications
10
55
1
1
Order By: Relevance
“…Nevertheless, it affords a uniquely detailed assessment of flow patterns in the heart and aorta. Validation studies have compared 4D PC‐MR with echocardiography in healthy volunteers and in patients without valvular disease (ie, subjects with laminar flow patterns), and found good agreement between both modalities . However, as previously reported by others, we found that systolic flow jets in AS patients are often eccentric .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Nevertheless, it affords a uniquely detailed assessment of flow patterns in the heart and aorta. Validation studies have compared 4D PC‐MR with echocardiography in healthy volunteers and in patients without valvular disease (ie, subjects with laminar flow patterns), and found good agreement between both modalities . However, as previously reported by others, we found that systolic flow jets in AS patients are often eccentric .…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, the entire acquired volume can be analyzed in a search for the highest flow jet velocity. In healthy volunteers and patients with normally functioning valves, 4D PC‐MR has shown improved flow quantification relative to echo . We hypothesized that in AS patients, who often exhibit eccentric and dynamic flow jets, the technical features of 4D PC‐MR could be even more advantageous .…”
mentioning
confidence: 99%
“…Positioning and orienting analysis planes in 3-D space at one or more specific anatomical locations as an additional post-processing step can be time consuming and also result in poor reproducibility across subjects and between operators due to its operator dependence. Volumetric ROI analysis, as used in our study as well as others, 11, 25 can reduce operator dependence and the risk of missing the true systolic peak velocity. Systolic flow patterns, which can give a qualitative sense of hemodynamics, as has been shown in other work investigating the relationship between flow patterns and energy loss, 26 are readily apparent in 4D flow MIPs.…”
Section: Discussionmentioning
confidence: 71%
“…Previous studies have shown that the technique can reliably identify altered 3D flow characteristics related to the post-interventional status in patients with CHD 149-152 . In addition, 4D flow MRI based flow quantification has been shown to be equivalent or even improved when compared to 2D techniques, while needing less imaging time than the positioning of multiple planes 58,61,64,67,68 . More recent developments combining parallel imaging or compressed sensing with 4D flow MRI have high potential to reduce scan times to <5 minutes.…”
Section: Applicationsmentioning
confidence: 99%